(x-6)(x+5)(x-6)=

Simple and best practice solution for (x-6)(x+5)(x-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)(x+5)(x-6)= equation:


Simplifying
(x + -6)(x + 5)(x + -6) = 0

Reorder the terms:
(-6 + x)(x + 5)(x + -6) = 0

Reorder the terms:
(-6 + x)(5 + x)(x + -6) = 0

Reorder the terms:
(-6 + x)(5 + x)(-6 + x) = 0

Multiply (-6 + x) * (5 + x)
(-6(5 + x) + x(5 + x))(-6 + x) = 0
((5 * -6 + x * -6) + x(5 + x))(-6 + x) = 0
((-30 + -6x) + x(5 + x))(-6 + x) = 0
(-30 + -6x + (5 * x + x * x))(-6 + x) = 0
(-30 + -6x + (5x + x2))(-6 + x) = 0

Combine like terms: -6x + 5x = -1x
(-30 + -1x + x2)(-6 + x) = 0

Multiply (-30 + -1x + x2) * (-6 + x)
(-30(-6 + x) + -1x * (-6 + x) + x2(-6 + x)) = 0
((-6 * -30 + x * -30) + -1x * (-6 + x) + x2(-6 + x)) = 0
((180 + -30x) + -1x * (-6 + x) + x2(-6 + x)) = 0
(180 + -30x + (-6 * -1x + x * -1x) + x2(-6 + x)) = 0
(180 + -30x + (6x + -1x2) + x2(-6 + x)) = 0
(180 + -30x + 6x + -1x2 + (-6 * x2 + x * x2)) = 0
(180 + -30x + 6x + -1x2 + (-6x2 + x3)) = 0

Combine like terms: -30x + 6x = -24x
(180 + -24x + -1x2 + -6x2 + x3) = 0

Combine like terms: -1x2 + -6x2 = -7x2
(180 + -24x + -7x2 + x3) = 0

Solving
180 + -24x + -7x2 + x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 30u^5*w^9+18u*w^2*x^7= | | x/2/3=1/2/1/4 | | 2+5b-2a-b= | | (6x-5)(2-3x)= | | .073=x(.285) | | (216)^8/(6)^3 | | 5(8r+5)-5r=-31+7r | | (216)power8/(6power2)power3 | | 25-32= | | (216)^8/(6^2)^3 | | 162=6(7+4v) | | 2senx-3cotx=0 | | 2.5x/12x | | 155=5(-6a-5) | | -2+3y-8y+3x= | | 6-5n=-(n-6) | | 40r-5r+7r= | | (2x+5)=x+3 | | 4x(3x-1)-6(2x+1)= | | 3/10=-8/5-n | | 30/7x=-255/28 | | sec(2x)+tan(x)=1 | | a-(-16)=11 | | 5c^3-15c^2+10c=0 | | 3r+9=-3(8r-3) | | 3r+9=24+9 | | 7+15x+2x^2= | | log(5)(5x+6)=2 | | tanx=cotx | | 0.5r+7=9 | | -4c+4c-2= | | -5(7r+5)=31-7r |

Equations solver categories